1995
DOI: 10.1002/j.2161-007x.1995.tb01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Satanism: Rebellion Masquerading as Religion

Abstract: This article describes adolescent satanic practice as studied by the authors working with affected families in 3 Southwestern states in a 7‐year period. Because adolescent involvement in satanism seems to be widespread and may be growing, counselors need to understand how satanism is related to religion, family dynamics, and adolescent rebellion. Counselors also need to recognize how their personal values compare with values inherent in satanism; only from a position of psychological equilibrium can counselors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Various studies have shown that this type of satanism is a form of rebellion for these young people, who are often very solitary characters with a low sense of self‐worth and power, deprived of affection. It gives them a feeling of belonging to a group and a sense of power . The juvenile satanism phenomenon is inspired more by deviation than by true or pseudoreligion.…”
mentioning
confidence: 99%
“…Various studies have shown that this type of satanism is a form of rebellion for these young people, who are often very solitary characters with a low sense of self‐worth and power, deprived of affection. It gives them a feeling of belonging to a group and a sense of power . The juvenile satanism phenomenon is inspired more by deviation than by true or pseudoreligion.…”
mentioning
confidence: 99%